PF-20 Successful Surgical Restoration with Enterorrhaphy after Rectal Prolapse in Experimental Animals - Hidetoshi Ishibashi (Hemera Zoa, 2018)
Complete rectal prolapse is the protrusion of the entire thickness of the rectal wall through the anal sphincter complex. Women aged 50 and older are 6 times as likely as men to present rectal prolapse. Two thirds of women patients are multiparous and 15 to 30% report associated urinary dysfunction and vaginal prolapse.The common marmoset (Callithrix jacchus) has been used increasingly in recent years for studies in bio-medical fields. The primate institute in National Center of Neurology and Psychiatry Japan was founded in 2005. Since then the number of marmoset gradually increased and 320 to 350 marmosets were housed in 2012. Averaged number of housed marmosets throughout the period is about 300. In the history of the institute, two cases of traumatic rectal prolapse, which had not been reported in marmosets, were found. This paper reports the etiology and the possible surgical treatment of marmoset rectal prolapse.